THE EFFECT OF NON-PERFORMA LOAN AND OPERATIONAL COST OF OPERATIONAL INCOME ON EARNING PER SHARE THROUGH RETURN ON IN PT. BANK SAHABAT SAMPOERNA - Dwi Ari Setyowati; Suharto Suharto; Harry Indratjahyo (The Institute of Academic Research and Publication (IARP), 2020)
This study aims to: 1) To test and analyze the influence of Non-Performance Loans (NPLs) and Operating Costs Operating Income (BOPO) on Return On Equity (ROE) at PT Bank Sahabat Sampoerna, 2) To test and analyze the influence of Non-Performance Loans ( NPL) and Operational Costs Operating Income (BOPO) on the Earning Per Share (EPS) of PT Bank Sahabat Sampoerna, 3) To test and analyze the effect of Return On Equity (ROE) on the Earning Per Share (EPS) of PT Bank Sahabat Sampoerna, 4) To test and analyze Non-Performance Loans (NPL) ), on the Earning Per Share (EPS) through PT Bank Sahabat Sampoerna's Return On Equity (ROE) variable and 5) To test and analyze the Operating Cost of Operating Income (BOPO) on the Earning Per Share (EPS) through PT Bank Sahabat Sampoerna's Return On Equity (ROE). This study uses secondary data, namely data obtained from the annual report of Bank Sahabat Sampoerna from 2015 - 2018. PT Bank Sahabat Sampoerna with a research sample of 48. The sampling technique uses random sampling techniques. The data analysis method uses descriptive analysis and path analysis. The results showed that: 1) there was the influence of Non-Performance Loans (NPL) and Operational Income Operating Costs (BOPO) on Return On Equity (ROE) at PT Bank Sahabat Sampoerna, 2) there wasn't an influence of Non-Performance Loans (NPL) and Operating Costs Operational (BOPO) on PT Bank Sahabat Sampoerna's Earning Per Share (EPS), 3) Return on Equity (ROE) not influence on PT Bank Sahabat Sampoerna's Earning Per Share, 4) No Non-Performance Loan (NPL) effect, on the Earning Per Share through the Return On Equity variable (ROE) of PT Bank Sahabat Sampoerna and 5) there is no effect of Operational Income Operating Costs (BOPO) on the Earning Per Share (EPS) through the Return on Equity (ROE) of PT Bank Sahabat Sampoerna.